Case report: Complete response of an anaplastic thyroid carcinoma patient with NRAS Q61R/BRAF D594N mutations to the triplet of dabrafenib, trametinib and PD-1 antibody - Gui, Lin; Zhu, Yiming; Li, Xiaomo; He, Xiaohui; Ma, Tonghui; Cai, Yi; Liu, Shaoyan (Frontiers in Immunology, 2023)
Abstract Anaplastic thyroid carcinoma (ATC) is a rare type of thyroid cancer with a mortality rate near 100%. BRAF V600 and NRAS mutations are the most common drivers of ATC. While patients with BRAF V600-mutated ATC can be treated with BRAF-targeted therapy, there is no effective treatment for ATC driven by NRAS or non-V600 BRAF mutations. For patients with untargetable driver mutations, immunotherapy provides an alternative treatment option. Here, we present a metastatic ATC patient with PD-L1 positive (tumor proportion score of 60%) tumor and NRAS Q61R/BRAF D594N mutations, who progressed on PD-1 antibody sintilimab plus angiogenesis inhibitor anlotinib. The class 3 BRAF mutant D594N is sensitive to the inhibition of MEK inhibitor trametinib, and its oncogenic activity also depends on CRAF, which can be inhibited by BRAF inhibitor dabrafenib. For these reasons, the patient received a salvage treatment regime of dabrafenib, trametinib, and sintilimab, which resulted in a complete pathological response. To our best knowledge, this is the first report of successful treatment of ATC patients with concurrent NRAS/BRAF non-V600 mutations with the combination of immunotherapy and targeted therapy. Further investigation is required to decipher the mechanism by which the combination of dabrafenib/trametinib with PD-1 antibody overcomes initial immunotherapy resistance likely mediated by concurrent BRAF and NRAS mutations.